معاملة السجين في الشريعة الإسلامية والقانون الليبي (لسنة1373,1988.1997)(دراسة نظرية وواقعية(Mu'aamalat assajin Fi assyari'at Al_Islamiyah Wa Al-Qonun al-Liby Dirosat nadzotiyah Wa Waqi'iyah - Jummah, Aynass Ahmed, Dr. M. Abdul Kholiq Hasan, M.A., M.Ed, Dr. M. Khairuddin Hamsin (2015)
This Letter Is an Inductive Analytic Research The Idea Was Born Because Of The Need In The Libyan Society To Know And Clarify How To Treat With The Prisoner In The Libyan Law And The Compatibility/Conflict With Islamic Law In Deal With The Prisoner. Research Focused On The Prisoner Issue Between The Libyan Law And Islamic Law And How They Are Agreed or Disagree With Each Other. The research focuses on The Compatibility and Opposes between Libyan Law Abuses Occurring in Libyan Prisons which not acceptable In Islamic Law. After Research, Study And Analysis In The Words Of Scientists And Scholars The Former And Contemporaries, As Well As The Study And Analysis Of Law Materials in Libya, The Researcher Found That The Treatment Of The Prisoner In reality Inside The Libyan Prisons Does Not Apply With The Treatment Of The Prisoner In Islamic Law. As Well as Some of the Material had direct Disagreement with the Provisions of Islamic Sharia Law. And That Some Of The Material Which Has The Kind Of Compassion in Sharia Has Provided Courtesy, As International Protocols To Libya Be A State Of Justice And Truth.